Sustainability of poultry egg output and efficiency: a risk-mitigating perspective - Ayojimi, Wale; Bamiro, Olasunkanmi M.; Otunaiya, Abiodun O.; Shoyombo, Ayoola J.; Matiluko, Opeyemi E. (Frontiers in Sustainable Food Systems, 2023)
Introduction Agricultural insurance is crucial to reducing financial exposures and vulnerabilities, and managing the production risks of poultry farmers while also reducing hunger levels. Unfortunately, it has not been effective in developing countries, like Nigeria. Methods This study examined the outcome of agricultural insurance use on poultry egg output and efficiency in Oyo State, Nigeria. The multistage sampling technique was adopted to select 120 and 152 insured and uninsured poultry egg farmers, respectively. The data gathered, using a well-designed questionnaire, was analyzed by descriptive statistics, a logistic regression model, and a Stochastic Production Frontier. Results and Discussion Results showed that the majority (about 74% and 77%) of uninsured and insured poultry egg farmers, respectively, were small-scale farmers who operated on low capital investment, making it difficult to take insurance policy. Educational level, farming size, access to credit facilities, previous mortality rate, sales challenges, and net farm income were significant variables affecting the level of use of insurance. The result of the stochastic production frontier showed that the use of insurance is not statistically significant to the poultry egg farmers’ production inefficiency. This study highlights the importance of formulating policies that promote private sector involvement, ensure prompt indemnity payment, and encourage uninsured farmers to adopt insurance policies, ultimately aiding affected farmers, improving production scale, and mitigating farm risks.